الخصائص المنھجیۃ للشیخ عبدالحکیم السیالکوتی فی ضوء حواشیہ: دراسۃ خاصۃ لحاشیتہ علی المطولMethodological Characteristics of Abdul Ḥakīm Siālkotī in the light of his Annotations: A Special Study of his Work on “Al-Mutawwal” (Al-Qamar, 2021)
“Al-Mutawwal” by Al-Taftāzānī (1322-1390), a Muslim Persian polymath, is a magnum opus on grammar, rhetoric, theology, logic, law and Qur’ānic exegesis. This linguistic work has been annotated and commented upon by numerous scholars. The present paper provides methodological characteristics of the annotation of “Al-Mutawwal” by Abdul Ḥakīm Siālkotī (1560-1657), a Muslim logician and philosopher of subcontinent and a friend and class fellow of renowned Indian scholar and Sufi Mujaddid Alf-e-Thānī Sheik Ahmad Sirhindī (1564-1624). It concludes that Siālkotī’s method is systematic and logical; he relies on original sources in rhetoric, grammar, language and literature. He has kept accuracy and honesty in mind while transmitting scholars’ opinions. His approach is characterized by freedom of opinion, extrapolation, scholarly circumspection and comprehensiveness. That’s why the referred annotation has been welcomed by the students and scholars of the relevant sciences across the globe.
Keywords: Al-Mutawwal; annotation; Siālkotī; characteristics